12X-6+3X+2=2X+3+13X-7

Simple and best practice solution for 12X-6+3X+2=2X+3+13X-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12X-6+3X+2=2X+3+13X-7 equation:


Simplifying
12X + -6 + 3X + 2 = 2X + 3 + 13X + -7

Reorder the terms:
-6 + 2 + 12X + 3X = 2X + 3 + 13X + -7

Combine like terms: -6 + 2 = -4
-4 + 12X + 3X = 2X + 3 + 13X + -7

Combine like terms: 12X + 3X = 15X
-4 + 15X = 2X + 3 + 13X + -7

Reorder the terms:
-4 + 15X = 3 + -7 + 2X + 13X

Combine like terms: 3 + -7 = -4
-4 + 15X = -4 + 2X + 13X

Combine like terms: 2X + 13X = 15X
-4 + 15X = -4 + 15X

Add '4' to each side of the equation.
-4 + 4 + 15X = -4 + 4 + 15X

Combine like terms: -4 + 4 = 0
0 + 15X = -4 + 4 + 15X
15X = -4 + 4 + 15X

Combine like terms: -4 + 4 = 0
15X = 0 + 15X
15X = 15X

Add '-15X' to each side of the equation.
15X + -15X = 15X + -15X

Combine like terms: 15X + -15X = 0
0 = 15X + -15X

Combine like terms: 15X + -15X = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3(s+1)-s=1 | | 24+x=7 | | (Y^-2/3)^-4/3 | | 3u=72-5u | | 2y+8x=11 | | 6320=90x+2000 | | 5n-5=3n+19 | | P(x)=3x^4+3x^5-6 | | 2c+3=6y | | y=90(300)+2000 | | 4+0.5t+2t=2.5 | | 5(M-6)+6(M-22)=3 | | y=90(200)+2000 | | y=90(100)+2000 | | 7+12x=-12+x | | 4a+7a+2a= | | (3x^4)^-4((1/9x^8)^-1)^2 | | 221-x=115 | | 10+1x=3x | | -13+x^2-6x=0 | | 170=-x+77 | | 12t+4=20 | | 24x=127 | | -20=7-3x | | 5(x-5)=5x+14 | | 158-u=282 | | -13+2x-6x=0 | | http://a.files.bbci.co.uk/equation-chef/live/7831083e7a760ce4180ffd8616dfc64f/18 | | x+(0.5x)=12 | | -5x-9y=17 | | 6+8y-5=9y+41-6y | | 6/8=12 |

Equations solver categories